2019
DOI: 10.1186/s13023-019-1153-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical burden of illness in patients with phenylketonuria (PKU) and associated comorbidities - a retrospective study of German health insurance claims data

Abstract: Background Phenylketonuria (PKU) is an inherited deficiency in the enzyme phenylalanine hydroxylase (PAH), which, when poorly-managed, is associated with clinical features including deficient growth, microcephaly, seizures, and intellectual impairment. The management of PKU should start as soon as possible after diagnosis to prevent irreversible damage and be maintained throughout life. The aim of this study was to assess the burden of illness in PKU patients in general and in PKU patients born be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 42 publications
2
58
1
2
Order By: Relevance
“…Over 30% of SLPF subgroups contained more salt than regular foods, with some containing 100-1050% extra. It is possible that their habitual consumption may contribute to nutritional co-morbidities such as hypertension [32][33][34], vascular stiffness [34,35], overweight/obesity [3,34,[36][37][38][39][40] and an atherogenic lipoprotein profile [34].…”
Section: Discussionmentioning
confidence: 99%
“…Over 30% of SLPF subgroups contained more salt than regular foods, with some containing 100-1050% extra. It is possible that their habitual consumption may contribute to nutritional co-morbidities such as hypertension [32][33][34], vascular stiffness [34,35], overweight/obesity [3,34,[36][37][38][39][40] and an atherogenic lipoprotein profile [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the literature currently leaves several intriguing questions (Box ). Relevant is a very recent study of German Insurance claims, including AwPKU (aged range 18‐96 years) and matched controls . 43% were early treated, though not all remained on diet, and few were receiving BH4.…”
Section: Discussionmentioning
confidence: 99%
“…Infants are diagnosed with PKU shortly after birth and avoiding aspartame is achieved well by patients throughout life [31]. However, people with PKU do show increased oxidative stress [32] and the presence of comorbidities including asthma, alopecia, urticaria, gallbladder disease, rhinitis, esophageal disorders, anemia, overweight, GERD, eczema, renal insufficiency, osteoporosis, gastritis/esophagitis and kidney stones [33]. Methanol, which is converted to formaldehyde (a known carcinogen) [34], is often pointed to as a reason to avoid aspartame, but higher levels of methanol are consumed when eating fruit [35,36].…”
Section: Aspartamementioning
confidence: 99%
“…Sucralose was found to promote fat accumulation and upregulate adipogenesis, inflammation, and antioxidant pathways [71]. While rodents lacking sweet taste receptor subunits were shown to have less adiposity and smaller adipocytes on a Western diet [32], showing the importance of sweet taste receptor signaling for normal adipose tissue development. One study suggested NNS's were not dependent on sweet taste receptors to stimulate adipogenesis or suppress lipolysis [36].…”
Section: Nutrient Sensingmentioning
confidence: 99%